Impact of Dialysis Method on Colon Postpolypectomy Bleeding in Patients with End-stage Renal Disease - , Hsueh-Chien Chiang, Hsueh-Chien Chiang, Chien-Ming Chiang, Xi-Zhang Lin, Po-Jun Chen (Turkish Journal of Gastroenterology 1, 2024)
Cite this article as: Chiang H, Chiang C, Lin X, Chen P. Impact of dialysis method on colon postpolypectomy bleeding in patients with end-stage renal disease. Turk J Gastroenterol. 2024;35(8):677-680.